Terapia Asistida con Animales para el Tratamiento de Mujeres Víctimas de Violencia de Género, Desde la Teoría del Apego Revisión Sistemática (2004-2024) (2024)
The research is a quantitative systematic review with a descriptive and empiricalanalytical approach, using the PRISMA 2020 and Cochrane guidelines, the objective was to identify the advancements of Animal-Assisted Therapy (AAT) in the treatment of women victims of gender-based violence in Colombia between 2004 and 2024, under the humanistic model and attachment theory.